Combustion characteristic of 2, 3, 3, 3-tetrafluroropropene (R1234yf). (December 2022) - Zhai, Rui; Yang, Zhao; Zhuang, Yuan; Ye, Bin; Tang, Jingchun
Highlights: The schematic mechanism for R1234yf combustion were revealed in unimolecular lysis reactions, colliding reactions with oxygen molecules, collision reaction with active radicals (H and OH radicals). The new chemical reaction equations for the combustion of R1234yf were proposed. This paper provided an effective method to establish the combustion mechanism of flammable hydrofluoroolefins. Abstract: To describe the combustion process of hydrofluoroolefins (HFOs) 2, 3, 3, 3-tetrafluroropropene (R1234yf), a kinetics mechanism was developed. On the M06–2X/6–311++ G (d, p) level, dynamic calculations have been performed using the density function theory (DFT) method. Proposed R1234yf kinetic reactions included unimolecular decomposition and intermolecular reactions, such as collisions with O2, OH, and H radicals. The results indicated that R1234yf combustion is a step-by-step chain reaction involving chain initiation (unimolecular lysis and collision reaction with oxygen), chain transmission (collision reactions with free radicals), and chain termination. In conjunction with the priority rule of kinetics reactions, a schematic diagram of the primary microscopic combustion pathways for R1234yf was created at 298.15 K and 1 atm. All the simulation results could provide a data basis to establish the kinetic model of hydrofluoroolefin pyrolysis and combustion. In addition, to verify the product direction of the reaction path, experiments were conducted to determine the properties of the R1234yf combustion products. Graphical abstract: Image, graphical abstract